Topography and climate shape ecosystem distribution across Tierra del Fuego, Argentina: insights from high-resolution modelling - Julián Rodríguez-Souilla; Pablo Luis Peri; Roberto Leónidas Lizárraga; Guillermo José Martínez Pastur (Polar Biology, 2026)

Modelling of cow-calf systems under land-sharing and land-sparing strategies in the Argentinean Chaco - Iván Daniel Filip; José Nasca; Natalia Banegas; Mónica Sacido; Pablo Peri; Claudia Faverin; Ronaldo Vibart (Journal of Environmental Management, 2026)

Modelling woody carbon dynamics in tropical dry forests: A case study of the Dry Chaco Region - Iván Daniel Filip; Pablo Luis Peri; Pedro Fernández; Dante Loto; Sebastián Miguel Kees; Natalia Banegas; José Nasca; Mónica Sacido; Claudia Faverin; Ronaldo Vibart (Ecological Modelling, 2026)

The Human Biomonitoring Project of the Valencian Region, Spain (BIOMOVAL): Study Design, Sampling, Fieldwork Results and Lessons Learned - Sandra F. Fernández; Pablo Dualde; Iñaki Lacomba; Vicent Yusà; Olga Pardo; Borja Peris-Camarasa; Maria Ibañez; Clara Coscollà (Exposure and Health, 2026)

Drivers and spatial modelling of soil organic carbon in Argentinian subtropical forests: Path towards sustainable management and climate mitigation - Silvina M. Manrique; Juan Gaitán; Ezequiel Balducci; Flavio Speranza; Cecilia Blundo; Ignacio Gasparri; Miguel A. Zavala; Pablo L. Peri (Forest Ecology and Management, 2025)

Fire and roller-chopping effects on forage production, plant diversity, and carbon storage in Neltuma woodlands of the Central Monte, Argentina - Pablo A. Meglioli; Marina A. Morsucci Labiano; Sebastián Mora; Leandro M. Alvarez; Gualberto Zalazar; Pablo L. Peri; Pablo E. Villagra (Agriculture, Ecosystems & Environment, 2025)

Direct Drivers of Spontaneous Exotic Plant Richness in Southern Patagonia from Argentina - Pablo L. Peri; Brenton Ladd; Romina Lasagno; Sandra Duarte Guardia; María Vanessa Lencinas; Guillermo Martínez Pastur (Current Landscape Ecology Reports, 2025)

Biomonitoring of Bisphenols, Parabens, Benzophenone-3 and Triclosan in Human Urine of Spanish Adult Population: Risk Assessment and Predictors of Exposure - Borja Peris-Camarasa; Pablo Dualde; Clara Coscollà (Exposure and Health, 2025)

Smoking-induced increasing of oxidative stress in Spanish adults: A urinary biomonitoring study. - Borja Peris-Camarasa; Iván Claros Garrido; Olga Pardo; Francesc A. Esteve-Turrillas; Pablo Dualde; Clara Coscollà (Environmental Toxicology and Pharmacology, 2025)

Current trends in silvopastoral systems - Pablo L. Peri; Julián Chará; Carolina Viñoles; Adriana Bussoni; Frederick Cubbage (Agroforestry Systems, 2024)

Changes derived by the silvopastoral management in Nothofagus antarctica forests of Tierra del Fuego compared to other productive environments - Guillermo Martínez Pastur; Yamina Micaela Rosas; Juan Manuel Cellini; Alejandro Huertas Herrera; Mónica D. R. Toro-Manríquez; María Vanessa Lencinas; Julieta Benítez; Sebastián Pechar; Pablo Luis Peri (Agroforestry Systems, 2024)

Response of forage production to drought in silvopastoral systems in Argentina - Pablo L. Peri; Santiago Toledo; Luis Gándara; Fabio Trinco; Marcos A. Atanasio; Noelia C. Calamari; Edgardo Casaubon; Natalia Martínez; Roxana Ledesma; Federico Gomez; Javier Lara; Lisandro Blanco; et al. (Agroforestry Systems, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Risk assessment and predictors of the exposure to polycyclic aromatic hydrocarbons in Spanish adults by urinary human biomonitoring - Borja Peris-Camarasa; Olga Pardo; Sandra F. Fernández; Pablo Dualde; Clara Coscollà (Chemosphere, 2024)

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

Mineral fertilization impacts microbial activity and endophytic fungi but not microbial biomass in semiarid grasslands - Santiago Toledo; Veronica Gargaglione; Pablo L. Peri (Pedobiologia, 2024)

Change of soil carbon storage in monoculture tree plantations across wide environmental gradients: Argentina as a case study - Javier Gyenge; Gabriel Gatica; Martín Sandoval; Ana María Lupi; Matías Gaute; María Elena Fernández; Pablo Luis Peri (Forest Ecology and Management, 2024)

Environmental factors regulate soil microbial attributes and their response to drought in rangeland ecosystems - Santiago Toledo; Viviana F. Bondaruk; Laura Yahdjian; Gastón R. Oñatibia; Alejandro Loydi; Juan Alberti; Martín Bruschetti; Jesús Pascual; Guadalupe Peter; Walter D. Agüero; Pedro R. Namur; Lisandro Blanco; et al. (Science of The Total Environment, 2023)

Variable retention harvesting and climate variations influence over natural regeneration dynamics in Nothofagus pumilio forests of Southern Patagonia - Julián Rodríguez-Souilla; Juan M. Cellini; María V. Lencinas; Fidel A. Roig; Jimena E. Chaves; Marie-Claire Aravena Acuña; Pablo L. Peri; Guillermo J. Martínez Pastur (Forest Ecology and Management, 2023)

Assessment of acrylamide exposure in Spain by human biomonitoring: Risk and predictors of exposure - Borja Peris-Camarasa; Olga Pardo; Sandra F. Fernández; Pablo Dualde; Clara Coscollà (Environmental Pollution, 2023)

Differential responses of soil microorganisms to precipitation changes in austral semiarid grasslands - Santiago Toledo; Veronica Gargaglione; Laura Yahdjian; Pablo L. Peri (Pedobiologia, 2023)

Potential biodiversity map of bird species (Passeriformes): Analyses of ecological niche, environmental characterization and identification of priority conservation areas in southern Patagonia - Yamina Micaela Rosas; Pablo L. Peri; Julieta Benítez; María Vanessa Lencinas; Natalia Politi; Guillermo Martínez Pastur (Journal for Nature Conservation, 2023)

Seed fall and leaf litter relationships in Nothofagus pumilio forests: changes according to retention levels and years after harvesting - Julián Rodríguez-Souilla; María V. Lencinas; Juan M. Cellini; Jimena E. Chaves; Fidel A. Roig; Pablo L. Peri; Guillermo J. Martínez Pastur (Trees, 2023)

A multi-model approach to explore sustainable food and land use pathways for Argentina - Federico Frank; José Volante; Noelia Calamari; Pablo L. Peri; Baltazar González Chávez; Pablo García Martínez; María J. Mosciaro; Gabriel Martín; Ignacio Benito Amaro; Ignacio Pace Guerrero; Karina Casellas; Melina Zuliani; et al. (Sustainability Science, 2023)

Future scenarios of land use change in the Gran Chaco: how far is zero-deforestation? - María Jesús Mosciaro; Noelia Cecilia Calamari; Pablo Luis Peri; Nelson Flores Montes; Lucas Seghezzo; Edder Ortiz; Larissa Rejalaga; Paula Barral; Sebastián Villarino; Matías Mastrangelo; José Volante (Regional Environmental Change, 2022)

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Changes in forest structure modify understory and livestock occurrence along the natural cycle and different management strategies in Nothofagus antarctica forests - Guillermo José Martínez Pastur; Juan M. Cellini; Jimena E. Chaves; Julián Rodríguez-Souilla; Julieta Benitez; Yamina M. Rosas; Rosina M. Soler; María V. Lencinas; Pablo L. Peri (Agroforestry Systems, 2022)

Nitrogen but not phosphorus addition affects symbiotic N2 fixation by legumes in natural and semi-natural grasslands located on four continents - Eduardo Vázquez; Per-Marten Schleuss; Elizabeth T. Borer; Miguel N. Bugalho; Maria C. Caldeira; Nico Eisenhauer; Anu Eskelinen; Philip A. Fay; Sylvia Haider; Anke Jentsch; Kevin P. Kirkman; Rebecca L. McCulley; et al. (Plant and Soil, 2022)
Background and aims The amount of nitrogen (N) derived from symbiotic N 2 fixation by legumes in grasslands might be affected by anthropogenic N and phosphorus (P) inputs, but the underlying mechanisms are not known. Methods We evaluated symbiotic N 2 fixation in 17 natural and semi-natural grasslands on four continents that are subjected to the same full-factorial N and P addition experiment, using the 15 N natural abundance method. Results N as well as combined N and P (NP) addition reduced aboveground legume biomass by 65% and 45%, respectively, compared to the control, whereas P addition had no significant impact. Addition of N and/or P had no significant effect on the symbiotic N 2 fixation per unit legume biomass. In consequence, the amount of N fixed annually per grassland area was less than half in the N addition treatments compared to control and P addition, irrespective of whether the dominant legumes were annuals or perennials. Conclusion Our results reveal that N addition mainly impacts symbiotic N 2 fixation via reduced biomass of legumes rather than changes in N 2 fixation per unit legume biomass. The results show that soil N enrichment by anthropogenic activities significantly reduces N 2 fixation in grasslands, and these effects cannot be reversed by additional P amendment.

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

MASTREE+: Time‐series of plant reproductive effort from six continents - Andrew Hacket‐Pain; Jessie J. Foest; Ian S. Pearse; Jalene M. LaMontagne; Walter D. Koenig; Giorgio Vacchiano; Michał Bogdziewicz; Thomas Caignard; Paulina Celebias; Joep van Dormolen; Marcos Fernández‐Martínez; Jose V. Moris; et al. (Global Change Biology, 2022)
Significant gaps remain in understanding the response of plant reproduction to environmental change. This is partly because measuring reproduction in long‐lived plants requires direct observation over many years and such datasets have rarely been made publicly available. Here we introduce MASTREE+, a data set that collates reproductive time‐series data from across the globe and makes these data freely available to the community. MASTREE+ includes 73,828 georeferenced observations of annual reproduction (e.g. seed and fruit counts) in perennial plant populations worldwide. These observations consist of 5971 population‐level time‐series from 974 species in 66 countries. The mean and median time‐series length is 12.4 and 10 years respectively, and the data set includes 1122 series that extend over at least two decades (≥20 years of observations). For a subset of well‐studied species, MASTREE+ includes extensive replication of time‐series across geographical and climatic gradients. Here we describe the open‐access data set, available as a.csv file, and we introduce an associated web‐based app for data exploration. MASTREE+ will provide the basis for improved understanding of the response of long‐lived plant reproduction to environmental change. Additionally, MASTREE+ will enable investigation of the ecology and evolution of reproductive strategies in perennial plants, and the role of plant reproduction as a driver of ecosystem dynamics.

Conservation values of understory vascular plants in even- and uneven-aged Nothofagus antarctica forests - Guillermo J. Martínez Pastur; Yamina M. Rosas; Juan M. Cellini; Marcelo D. Barrera; Mónica DR Toro Manríquez; Alejandro Huertas Herrera; Santiago Favoretti Bondar; María V. Lencinas; Pablo L. Peri (Biodiversity and Conservation, 2020)

Biophysical and socioeconomic factors influencing soil carbon stocks: a global assessment - Sandra Duarte-Guardia; Pablo Peri; Wulf Amelung; Evert Thomas; Nils Borchard; German Baldi; Annette Cowie; Brenton Ladd (Mitigation and Adaptation Strategies for Global Change, 2020)

Microbial processing of plant remains is co‐limited by multiple nutrients in global grasslands - Raúl Ochoa‐Hueso; Elizabeth T. Borer; Eric W. Seabloom; Sarah E. Hobbie; Anita C. Risch; Scott L. Collins; Juan Alberti; Héctor A. Bahamonde; Cynthia S. Brown; Maria C. Caldeira; Pedro Daleo; Chris R. Dickman; et al. (Global Change Biology, 2020)
Microbial processing of aggregate‐unprotected organic matter inputs is key for soil fertility, long‐term ecosystem carbon and nutrient sequestration and sustainable agriculture. We investigated the effects of adding multiple nutrients (nitrogen, phosphorus and potassium plus nine essential macro‐ and micro‐nutrients) on decomposition and biochemical transformation of standard plant materials buried in 21 grasslands from four continents. Addition of multiple nutrients weakly but consistently increased decomposition and biochemical transformation of plant remains during the peak‐season, concurrent with changes in microbial exoenzymatic activity. Higher mean annual precipitation and lower mean annual temperature were the main climatic drivers of higher decomposition rates, while biochemical transformation of plant remains was negatively related to temperature of the wettest quarter. Nutrients enhanced decomposition most at cool, high rainfall sites, indicating that in a warmer and drier future fertilized grassland soils will have an even more limited potential for microbial processing of plant remains.

Dominant native and non‐native graminoids differ in key leaf traits irrespective of nutrient availability - Arthur A. D. Broadbent; Jennifer Firn; James M. McGree; Elizabeth T. Borer; Yvonne M. Buckley; W. Stanley Harpole; Kimberly J. Komatsu; Andrew S. MacDougall; Kate H. Orwin; Nicholas J. Ostle; Eric W. Seabloom; Jonathan D. Bakker; et al. (Global Ecology and Biogeography, 2020)
Aim Nutrient enrichment is associated with plant invasions and biodiversity loss. Functional trait advantages may predict the ascendancy of invasive plants following nutrient enrichment but this is rarely tested. Here, we investigate (a) whether dominant native and non‐native plants differ in important morphological and physiological leaf traits, (b) how their traits respond to nutrient addition, and (c) whether responses are consistent across functional groups. Location Australia, Europe, North America and South Africa. Time period 2007–2014. Major taxa studied Graminoids and forbs. Methods We focused on two types of leaf traits connected to resource acquisition: morphological features relating to light‐foraging surfaces and investment in tissue (specific leaf area, SLA) and physiological features relating to internal leaf chemistry as the basis for producing and utilizing photosynthate. We measured these traits on 503 leaves from 151 dominant species across 27 grasslands on four continents. We used an identical nutrient addition treatment of nitrogen (N), phosphorus (P) and potassium (K) at all sites. Sites represented a broad range of grasslands that varied widely in climatic and edaphic conditions. Results We found evidence that non‐native graminoids invest in leaves with higher nutrient concentrations than native graminoids, particularly at sites where native and non‐native species both dominate. We found little evidence that native and non‐native forbs differed in the measured leaf traits. These results were consistent in natural soil fertility levels and nutrient‐enriched conditions, with dominant species responding similarly to nutrient addition regardless of whether they were native or non‐native. Main conclusions Our work identifies the inherent physiological trait advantages that can be used to predict non‐native graminoid establishment, potentially because of higher efficiency at taking up crucial nutrients into their leaves. Most importantly, these inherent advantages are already present at natural soil fertility levels and are maintained following nutrient enrichment.

Nutrient availability controls the impact of mammalian herbivores on soil carbon and nitrogen pools in grasslands - Judith Sitters; E. R. Jasper Wubs; Elisabeth S. Bakker; Thomas W. Crowther; Peter B. Adler; Sumanta Bagchi; Jonathan D. Bakker; Lori Biederman; Elizabeth T. Borer; Elsa E. Cleland; Nico Eisenhauer; Jennifer Firn; et al. (Global Change Biology, 2020)
Grasslands are subject to considerable alteration due to human activities globally, including widespread changes in populations and composition of large mammalian herbivores and elevated supply of nutrients. Grassland soils remain important reservoirs of carbon (C) and nitrogen (N). Herbivores may affect both C and N pools and these changes likely interact with increases in soil nutrient availability. Given the scale of grassland soil fluxes, such changes can have striking consequences for atmospheric C concentrations and the climate. Here, we use the Nutrient Network experiment to examine the responses of soil C and N pools to mammalian herbivore exclusion across 22 grasslands, under ambient and elevated nutrient availabilities (fertilized with NPK + micronutrients). We show that the impact of herbivore exclusion on soil C and N pools depends on fertilization. Under ambient nutrient conditions, we observed no effect of herbivore exclusion, but under elevated nutrient supply, pools are smaller upon herbivore exclusion. The highest mean soil C and N pools were found in grazed and fertilized plots. The decrease in soil C and N upon herbivore exclusion in combination with fertilization correlated with a decrease in aboveground plant biomass and microbial activity, indicating a reduced storage of organic matter and microbial residues as soil C and N. The response of soil C and N pools to herbivore exclusion was contingent on temperature – herbivores likely cause losses of C and N in colder sites and increases in warmer sites. Additionally, grasslands that contain mammalian herbivores have the potential to sequester more N under increased temperature variability and nutrient enrichment than ungrazed grasslands. Our study highlights the importance of conserving mammalian herbivore populations in grasslands worldwide. We need to incorporate local‐scale herbivory, and its interaction with nutrient enrichment and climate, within global‐scale models to better predict land–atmosphere interactions under future climate change.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Potential biodiversity map of darkling beetles (Tenebrionidae): environmental characterization, land-uses and analyses of protection areas in Southern Patagonia - Yamina Micaela Rosas; Pablo L. Peri; Rodolfo Carrara; Gustavo E. Flores; Julieta Pedrana; Guillermo Martínez Pastur (Journal of Insect Conservation, 2019)

Better estimates of soil carbon from geographical data: a revised global approach - Sandra Duarte-Guardia; Pablo L. Peri; Wulf Amelung; Douglas Sheil; Shawn W. Laffan; Nils Borchard; Michael I. Bird; Wouter Dieleman; David A. Pepper; Brian Zutta; Esteban Jobbagy; Lucas C. R. Silva; et al. (Mitigation and Adaptation Strategies for Global Change, 2019)

Soil microbial processes in a pine silvopastoral system in NW Patagonia - Marina Gonzalez-Polo; Héctor A. Bahamonde; Pablo L. Peri; María Julia Mazzarino; Clara Fariña; Gonzalo Caballé (Agroforestry Systems, 2019)

Spatial heterogeneity in species composition constrains plant community responses to herbivory and fertilisation - Dorothee Hodapp; Elizabeth T. Borer; W. Stanley Harpole; Eric M. Lind; Eric W. Seabloom; Peter B. Adler; Juan Alberti; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Marc Cadotte; Elsa E. Cleland; et al. (Ecology Letters, 2018)
Environmental change can result in substantial shifts in community composition. The associated immigration and extinction events are likely constrained by the spatial distribution of species. Still, studies on environmental change typically quantify biotic responses at single spatial (time series within a single plot) or temporal (spatial beta diversity at single time points) scales, ignoring their potential interdependence. Here, we use data from a global network of grassland experiments to determine how turnover responses to two major forms of environmental change – fertilisation and herbivore loss – are affected by species pool size and spatial compositional heterogeneity. Fertilisation led to higher rates of local extinction, whereas turnover in herbivore exclusion plots was driven by species replacement. Overall, sites with more spatially heterogeneous composition showed significantly higher rates of annual turnover, independent of species pool size and treatment. Taking into account spatial biodiversity aspects will therefore improve our understanding of consequences of global and anthropogenic change on community dynamics.

North‐west Africa as a source and refuge area of plant biodiversity: a case study on Campanula kremeri and Campanula occidentalis - Sara García‐Aloy; Daniel Vitales; Cristina Roquet; Isabel Sanmartín; Pablo Vargas; Julián Molero; Peris Kamau; Juan José Aldasoro; Marisa Alarcón (Journal of Biogeography, 2017)
Aim North‐west Africa, because of its position at the crossroads between Macaronesia and the Iberian Peninsula, has played an important role on the emergence and maintenance of Mediterranean plant diversity. In this study, we reconstruct the phylogeographical history of a lineage of bellflowers comprising the north African‐south Iberian species Campanula kremeri and the Canarian Campanula occidentalis ( Azorina ‐group), to investigate the genetic imprints left by past climatic and palaeogeographical events on the northern African flora. Location North‐west Africa, Iberian Peninsula, and the Canary Islands. Methods We reconstructed the biogeographical history of the Azorina ‐group to provide a phylogenetic background. We then investigated the phylogeographical patterns within C. kremeri and C. occidentalis using the AFLP and sequence data. We integrated these results with the past species‐distribution modelling to understand the current biodiversity patterns within this lineage. Results The ancestor of C. kremeri ‐ C. occidentalis diverged in the Late Miocene/Early Pliocene. Nuclear data supported species monophyly, whereas plastid data suggested that C. kremeri is paraphyletic. Maghrebian populations of C. kremeri showed high genetic diversity, whilst Iberian ones and those of C. occidentalis exhibited lower values. Main conclusions Repeated expansion‐retraction events associated with Pleistocene climatic changes in North Africa facilitated gene flow across Maghrebian ranges in C. kremeri . Mountain massifs in north‐west Africa likely acted as refugia for Mediterranean plants during interglacial periods, whereas range expansion in cooler periods triggered dispersal to neighbouring regions. The range of C. kremeri expanded to the Iberian Peninsula by long‐distance dispersal across the Strait of Gibraltar during the Pleistocene. The relatively old age inferred for C. occidentalis together with its low genetic diversity point to a recent colonization of the Canary Islands from north‐west Africa followed by extinction in the mainland or an old lineage that underwent a recent genetic bottleneck.

A review of silvopastoral systems in native forests of Nothofagus antarctica in southern Patagonia, Argentina - Pablo Luis Peri; Héctor A. Bahamonde; María V. Lencinas; Verónica Gargaglione; Rosina Soler; Sebastián Ormaechea; Guillermo Martínez Pastur (Agroforestry Systems, 2016)

Biodiversity potential of Nothofagus forests in Tierra del Fuego (Argentina): tool proposal for regional conservation planning - Guillermo Martínez Pastur; Pablo L. Peri; Rosina M. Soler; Stefan Schindler; María Vanessa Lencinas (Biodiversity and Conservation, 2016)

BAAD: a Biomass And Allometry Database for woody plants - Daniel S. Falster; Remko A. Duursma; Masae I. Ishihara; Diego R. Barneche; Richard G. FitzJohn; Angelica Vårhammar; Masahiro Aiba; Makoto Ando; Niels Anten; Michael J. Aspinwall; Jennifer L. Baltzer; Christopher Baraloto; et al. (Ecology, 2015)
Understanding how plants are constructed—i.e., how key size dimensions and the amount of mass invested in different tissues varies among individuals—is essential for modeling plant growth, carbon stocks, and energy fluxes in the terrestrial biosphere. Allocation patterns can differ through ontogeny, but also among coexisting species and among species adapted to different environments. While a variety of models dealing with biomass allocation exist, we lack a synthetic understanding of the underlying processes. This is partly due to the lack of suitable data sets for validating and parameterizing models. To that end, we present the Biomass And Allometry Database (BAAD) for woody plants. The BAAD contains 259 634 measurements collected in 176 different studies, from 21 084 individuals across 678 species. Most of these data come from existing publications. However, raw data were rarely made public at the time of publication. Thus, the BAAD contains data from different studies, transformed into standard units and variable names. The transformations were achieved using a common workflow for all raw data files. Other features that distinguish the BAAD are: (i) measurements were for individual plants rather than stand averages; (ii) individuals spanning a range of sizes were measured; (iii) plants from 0.01–100 m in height were included; and (iv) biomass was estimated directly, i.e., not indirectly via allometric equations (except in very large trees where biomass was estimated from detailed sub‐sampling). We included both wild and artificially grown plants. The data set contains the following size metrics: total leaf area; area of stem cross‐section including sapwood, heartwood, and bark; height of plant and crown base, crown area, and surface area; and the dry mass of leaf, stem, branches, sapwood, heartwood, bark, coarse roots, and fine root tissues. We also report other properties of individuals (age, leaf size, leaf mass per area, wood density, nitrogen content of leaves and wood), as well as information about the growing environment (location, light, experimental treatment, vegetation type) where available. It is our hope that making these data available will improve our ability to understand plant growth, ecosystem dynamics, and carbon cycling in the world's vegetation.

Tree–grass interactions for N in Nothofagus antarctica silvopastoral systems: evidence of facilitation from trees to underneath grasses - Verónica Gargaglione; Pablo L. Peri; Gerardo Rubio (Agroforestry Systems, 2014)

Relating water use to morphology and environment of Nothofagus from the world’s most southern forests - Sebastian Pfautsch; Pablo L. Peri; Craig Macfarlane; Floris van Ogtrop; Mark A. Adams (Trees, 2014)

Are silvopastoral systems compatible with forest regeneration? An integrative approach in southern Patagonia - Rosina Soler; Guillermo Martínez Pastur; Pablo Peri; María Vanessa Lencinas; Fernando Pulido (Agroforestry Systems, 2013)

Estimates of soil carbon concentration in tropical and temperate forest and woodland from available GIS data on three continents - Brenton Ladd; Shawn W. Laffan; Wulf Amelung; Pablo L. Peri; Lucas C. R. Silva; Pina Gervassi; Stephen P. Bonser; Marcelo Navall; Douglas Sheil (Global Ecology and Biogeography, 2013)
Aim Concern about climate change, with the subsequent emergence of carbon markets and policy initiatives such as REDD (reducing carbon emissions by decreasing deforestation and forest degradation), have focused attention on assessing and monitoring terrestrial carbon reserves. Most effort has focused on above‐ground forest biomass. Soil has received less attention despite containing more carbon than above‐ground terrestrial biomass and the atmosphere combined. Our aim was to explore how well soil carbon concentration could be estimated on three continents from existing climate, topography and vegetation‐cover data. Location P eru, B razil, A rgentina, A ustralia, C hina. Methods Soil carbon concentration and leaf area index ( LAI ) as well as GIS ‐derived climate and topography variables for 65 temperate and 43 tropical, forest and woodland ecosystems, were either directly measured or estimated from freely available global datasets. We then used multiple regressions to determine how well soil carbon concentration could be predicted from LAI , climate and topography at a given site. We compared our measurements with top soil carbon estimates from the F ood and A griculture O rganization of the U nited N ations ( FAO ) harmonized world soil map. Results Our empirical model based on estimates of temperature, water availability and plant productivity provided a good estimate of soil carbon concentrations ( R 2 = 0.79). In contrast, the values of topsoil carbon concentrations from the FAO harmonized world soil map correlated poorly with the measured values of soil carbon concentration ( R 2 = 0.0011). Main conclusions The lack of correlation between the measured values of soil carbon and the values from the FAO harmonized world soil map indicate that substantial improvements in the production of soil carbon maps are needed and possible. Our results demonstrate that the inclusion of freely available GIS data offers improved estimates of soil carbon and will allow the creation of more accurate soil carbon maps.

Agroforestry landscapes and global change: landscape ecology tools for management and conservation - Guillermo Martínez Pastur; Emilie Andrieu; Louis R. Iverson; Pablo Luis Peri (Agroforestry Systems, 2012)

Carbon (δ 13 C ) and nitrogen (δ 15 N ) stable isotope composition in plant and soil in S outhern P atagonia's native forests - Pablo L. Peri; Brenton Ladd; David A. Pepper; Stephen P. Bonser; Shawn W. Laffan; Wulf Amelung (Global Change Biology, 2012)
Stable isotope natural abundance measurements integrate across several biogeochemical processes in ecosystem N and C dynamics. Here, we report trends in natural isotope abundance (δ 13 C and δ 15 N in plant and soil) along a climosequence of 33 N othofagus forest stands located within P atagonia, S outhern A rgentina. We measured 28 different abiotic variables (both climatic variables and soil properties) to characterize environmental conditions at each of the 33 sites. Foliar δ 13 C values ranged from −35.4‰ to −27.7‰, and correlated positively with foliar δ 15 N values, ranging from −3.7‰ to 5.2‰. Soil δ 13 C and δ 15 N values reflected the isotopic trends of the foliar tissues and ranged from −29.8‰ to −25.3‰, and −4.8‰ to 6.4‰, respectively, with no significant differences between N othofagus species ( N othofagus pumilio , N othofagus antarctica , N othofagus betuloides ). Principal component analysis and multiple regressions suggested that mainly water availability variables (mean annual precipitation), but not soil properties, explained between 42% and 79% of the variations in foliar and soil δ 13 C and δ 15 N natural abundance, which declined with increased moisture supply. We conclude that a decline in water use efficiency at wetter sites promotes both the depletion of heavy C and N isotopes in soil and plant biomass. Soil δ 13 C values were higher than those of the plant tissues and this difference increased as annual precipitation increased. No such differences were apparent when δ 15 N values in soil and plant were compared, which indicates that climatic differences contributed more to the overall C balance than to the overall N balance in these forest ecosystems.

Flowering and seeding patterns in primary, secondary and silvopastoral managed Nothofagus antarctica forests in South Patagonia - Rosina Soler Esteban; Guillermo Martínez Pastur; María Vanessa Lencinas; Pablo Luis Peri (New Zealand Journal of Botany, 2010)
The success of the reproductive process in trees depends on abiotic and biotic factors that determine the final outcome of natural regeneration. Silviculture alters biotic and abiotic factors and results in secondary forest structures. To effectively manage these forests, it is necessary to understand the bottlenecks in reproductive stages using a whole‐cycle approach study. The aim of this study was to analyse flowering and seeding patterns in primary, secondary and silvopastoral managed Nothofagus antarctica forests, including investigating the pre‐dispersion foraging of insects and birds, as well as abscised biomass production. A high percentage of female flowers produced fruits (95–96%) in which the main loss factor before seeding was the abscission of immature fruits (11–14%). Seeding was greater in secondary forests (11.4 million ha −1 ), but managed stands presented a higher percentage of flowers resulting in seeds (82%). However, secondary forests had a better seed quality (17% viable seeds), where the main loss factor was empty seeds in all treatments (39–50%). Biotic factors (foraging by insects and birds) were higher in disturbed than primary forests. Nothofagus antarctica produce large quantities of seeds, but abscised immature fruits and empty seeds due to self‐incompatibility mechanisms appeared as the major loss factors.

Windbreaks in southern Patagonia,Argentina: A review of research on growth models, windspeed reduction, and effects oncrops - Pablo Luis Peri; Mark Bloomberg (Agroforestry Systems, 2002)

Changes in Nothofagus pumilio forest biodiversity during the forest management cycle. 1. Insects - Carlos Spagarino; Guillermo Martínez Pastur; Pablo Peri (Biodiversity and Conservation, 2001)

Changes in Nothofagus pumilio forest biodiversity during the forest management cycle. 2. Birds - Guillermo Deferrari; Carolina Camilión; Guillermo Martínez Pastur; Pablo Luis Peri (Biodiversity and Conservation, 2001)